COMPARATIVE DIAGNOSTICS OF METHODS OF PROMOTION OF ORGANIC MARKET LEADERS ON THE INTERNET - SHAPORENKO, OLENA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article considers and analyzes the methods of promoting organic products on the Internet, which are used by leaders of the Ukrainian market. Over the past five years, the form of interaction between producers and consumers of organic products has changed radically, in particular, communication has come to a straight line without unnecessary intermediaries due to the latest opportunities on the Internet. The use of tools that have become more accessible to all market players - this question remains open, as well as the question of consumer readiness for direct interaction with the manufacturer. Characteristic differences of the selected vectors of work with consumers by users of a network are investigated. One of the trends of today is the great transition of retail to the Internet, over the past two years, the picture has changed radically. Of course, lockdown played a big role in this transition in 2020, but after its completion it became clear that manufacturers who did not pay enough attention to such a sales channel, when online sales were almost one of the opportunities to sell goods, far behind those who worked online and build relationships with its customers using all the capabilities and tools of the network. The main problems that hinder the correct interaction with the target audiences are identified. Organic product promotion tools such as brand ambassadors, lack of work with bloggers and opinion leaders, virtually no elements of loyalty programs for regular and potential customers are not used at all. Even the simplest gamification tools are missing. Taking into account the existing data, a number of recommendations for networking in the context of modern market conditions have been developed